2023
DOI: 10.1101/2023.10.30.564854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Principles of Computation by Competitive Protein Dimerization Networks

Jacob Parres-Gold,
Matthew Levine,
Benjamin Emert
et al.

Abstract: SummaryMany biological signaling pathways employ proteins that competitively dimerize in diverse combinations. These dimerization networks can perform biochemical computations, in which the concentrations of monomers (inputs) determine the concentrations of dimers (outputs). Despite their prevalence, little is known about the range of input-output computations that dimerization networks can perform (their “expressivity”) and how it depends on network size and connectivity. Using a systematic computational appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 132 publications
0
2
0
Order By: Relevance
“…While a single sigma-based perceptron generates a tunable decision boundary even with sharing limited resources (Fig. 3), most biologically relevant biocomputation processes such as competitive ligand binding and protein dimerization generate sophisticated non-linear responses that rely on the protein-protein interactions and the concentration of competing dimerizing proteins or ligands [18,17]. Therefore, we aim to utilize the sigma-based perceptron as a basic building block of more intricate networks made of multiple perceptrons that are capable of generating non-linear outputs.…”
Section: Biomolecular Neural Network Generate Non-linear Classifiers ...mentioning
confidence: 99%
See 1 more Smart Citation
“…While a single sigma-based perceptron generates a tunable decision boundary even with sharing limited resources (Fig. 3), most biologically relevant biocomputation processes such as competitive ligand binding and protein dimerization generate sophisticated non-linear responses that rely on the protein-protein interactions and the concentration of competing dimerizing proteins or ligands [18,17]. Therefore, we aim to utilize the sigma-based perceptron as a basic building block of more intricate networks made of multiple perceptrons that are capable of generating non-linear outputs.…”
Section: Biomolecular Neural Network Generate Non-linear Classifiers ...mentioning
confidence: 99%
“…Competitive binding of only a few promiscuous ligands to various receptors has been demonstrated to accommodate a wide range of signaling activities in multicellular organisms [17]. Similarly, it was recently shown that competitive protein dimerization allows small protein monomer networks to encode an extensive range of homo-or hetero-dimeric outputs through precise adjustments in the concentration of network monomers [18]. In addition, competing transcription factors that bind to the same RNA polymerase may affect the output of engineered genetic circuits in bacteria.…”
Section: Introductionmentioning
confidence: 99%